Biology concepts: photosynthesis - Goodman, Harvey D. (Educational Activities, 1997)
This program consists of instructional video units and a scientific inquiry section which includes both video segments and writing activities. The program also contains a vocabulary word list and review section, both of which are supported by video segments to give students reinforcement and immediate feedback.